Measuring Kinase Activity—A Global Challenge. Issue 11 (31st May 2017) - Cann, Marissa L.; McDonald, Ian M.; East, Michael P.; Johnson, Gary L.; Graves, Lee M.
ABSTRACT: The kinase enzymes within a cell, known collectively as the kinome, play crucial roles in many signaling pathways, including survival, motility, differentiation, stress response, and many more. Aberrant signaling through kinase pathways is often linked to cancer, among other diseases. A major area of scientific research involves understanding the relationships between kinases, their targets, and how the kinome adapts to perturbations of the cellular system. This review will discuss many of the current and developing methods for studying kinase activity, and evaluate their applications, advantages, and disadvantages. J. Cell. Biochem. 118: 3595–3606, 2017. © 2017 Wiley Periodicals, Inc. Abstract : The kinase enzymes within a cell, known collectively as the kinome, play crucial roles in many signaling pathways, including survival, motility, differentiation, stress response, and many more. A major area of scientific research involves understanding the relationships between kinases, their targets, and how the kinome adapts to perturbations of the cellular system. This review will discuss many of the current and developing methods for studying kinase activity, and evaluate their applications, advantages, and disadvantages.